A ratiometric fluorescent probe for quantification of alkaline phosphatase in living cells. Issue 38 (30th March 2016) - Lu, Zhenxing; Wu, Jiasheng; Liu, Weimin; Zhang, Guangyou; Wang, Pengfei
Abstract : A ratiometric fluorescent probe with strong intramolecular charge transfer (ICT) character has been designed for the detection of alkaline phosphatase (ALP). Abstract : A ratiometric fluorescent probe with strong intramolecular charge transfer (ICT) character has been designed for the detection of alkaline phosphatase (ALP). In the presence of ALP, probe1 showed a dramatic bathochromic shift from 550 to 650 nm in the fluorescence spectrum and an obvious ratiometric signal with an isoemissive point was observed. The spectral change was attributed to the hydrolysis and cleavage of a phosphate group from the probe that changed the ability of the intramolecular charge transfer. The fluorescence intensity ratio displayed a linear relationship against the concentration of ALP in the concentration range from 50 to 200 U L −1 . Other biological species, including lysozyme, trypsin, pepsin, acetyl cholinesterase, carboxylesterase, and bovine serum albumin, did not induce distinct spectral changes of the probe, indicating its selective sensing ability to ALP. Furthermore, probe1 was also successfully applied to image endogenous ALP activity in living cells.